Contextualized Vocabulary Teaching Strategy in Vocational Education: A Study on Effectiveness and Student Engagement - Susanto Susanto; Deri Sis Nanda (Educational Research Indonesia, 2025)
Vocabulary is a fundamental component of language proficiency and plays a crucial role in students’ ability to comprehend texts and communicate effectively. Effective vocabulary instruction requires the use of appropriate teaching strategies to support students in acquiring, retaining, and applying new words. The purpose of this study was to examine the strategies used by English teachers to teach vocabulary at SMK SWADHIPA 1 Natar, a vocational school in Lampung Province. A qualitative descriptive research design was used to explore instructional practices in depth. Data were collected through classroom observations and semi-structured interviews with two English teachers. Observations focused on vocabulary teaching during classroom activities, while interviews were conducted to gain further insights into the rationale behind the instructional approaches used. The findings revealed that both teachers utilized similar strategies, notably the use of contextual learning and repetition and reinforcement techniques, to enhance students’ vocabulary acquisition. These strategies were found to be effective in promoting student engagement and supporting long-term retention of new vocabulary, as evidenced by active student participation and the consistent use of 75–80% of newly introduced words during observed lessons. Furthermore, post-lesson assessments indicated a vocabulary retention rate of 82% among students. The results suggest that incorporating contextualized vocabulary instruction and repeated practice into vocational English curricula can better equip students with the language needed for specific workplace communication tasks.